Effect of an Educational Intervention for Nursing Personnel on Emergency Inventory and Drugs Checklist of Resuscitation Trolley in a Tertiary Cardiac Center, Kathmandu. - Khadka, Sunita; Shrestha, Battu Kumar; Thapa, Reshma; Saru, Deoki; Dangol, Nita Devi; Prajapati, Dipanker; Dhungana, Suraksha; Dhungana, Murari; Adhikari, Chandra Mani (Nepalese Heart Journal, 2023)
Background and Aims: A crash cart is a trolley with emergency medicines and equipments required for medical emergencies. Nurses often witness cardiac arrest. They should be familiar with the placement of equipments and drugs in crash cart trolleys. Thus, this study was conducted to assess the effect of an educational intervention on knowledge of crash cart drugs and equipment management among nurses. Methods: This is a pre-experimental research design conducted at Shahid Gangalal National Heart Center, Kathmandu, Nepal.A simple random sampling technique was adopted. A semi-structured questionnaire was used to identify the knowledge of nurses. A standard checklist was used to observe crash cart trolleys. Pre and post test data was taken. Outcome variables included knowledge of crash cart trolleys organization and well organized crash cart in diferent wards. Data were analyzed to compare the knowledge before and after the intervention. Chi-square test, pair t-test, and linear regression multivariable model used for statistical analysis. Results: A total of 134 nurses were recruited in this study. The overall mean score of knowledge was signifcantly higher in post-intervention. The total knowledge mean score difference among nurses was -11.07, (p<0.001), drug content difference at crash cart was -16.85, (p<0.001), equipment content at crash cart was -24.42, (p<0.001).The linear regression showed significant improvement in knowledge at post-intervention (β; 0.928, 95% CI; 10.52, 11.57, p<0.001), when adjusted for age, education, work experience, working unit and CPR training. Conclusion: Knowledge and organization of crash cart was improved after educational intervention.